Postpartum Anxiety and Intrapsychic Vulnerability Reflected by Early Maladaptive Schemas - Molnár, Judit; Kósa, Karolina; Fekete, Zita; Münnich, Ákos (European Journal of Mental Health, 2018)
The prevalence of postpartum anxiety is high and its negative consequences are significant. Most research studies have aimed at exploring the demographic and psychosocial risk factors while neglecting factors of intrapsychic vulnerability.The aim of our study is to examine postpartum anxiety from this aspect, that is, uncovering the early relational experiences of mothers, specifically regarding their early maladaptive schemas.Methods: 125 women participated in online data collection in the first year after giving birth. Maternal anxiety was measured with the postpartum version of STAI-S, while early maladaptive schemas were assessed with the Schema Questionnaire.Results: In terms of demographics, most of the mothers in our sample had middle-class characteristics, but 21.6% had clinical, and 34.4% had subclinical levels of anxiety. Our results confirmed a significant, direct effect of maladaptive schemas on postpartum anxiety in case of 13 of the 15 measured schemas.Discussion: This study draws attention to the intrapsychic vulnerability of mothers as a highly neglected etiological aspect of postpartum anxiety. Further research of intrapsychic and, especially, attachment-related vulnerability should be carried out to identify at-risk women and treat postpartum anxiety more adequately.Limitations: The sample consisted of highly educated, married women with planned children, so the results are not representative for mothers in general.